A Micro-Analytical Study of the Scarabs of the Necropolis of Vinha das Caliças (Portugal). (31st January 2019) - Costa, Mafalda; Arruda, Ana Margarida; Barbosa, Rui; Barrulas, Pedro; Vandenabeele, Peter; Mirão, José
Abstract: Five scarabs and one scaraboid found in Vinha das Caliças 4 (Beja, Portugal) were analyzed using a micro-analytical methodology in order to determine their mineralogical and chemical composition. Microstructural characterization and chemical analysis revealed that all were composed of a white body of crushed feldspathic sand covered by a lead-rich, alkaline-depleted silicate blue-green glaze showing evident signs of glass deterioration. Variable pressure scanning electron microscopy with X-ray energy dispersive spectrometry, handheld X-ray fluorescence spectroscopy, and micro X-ray diffraction results show that blue-green color of the glaze was produced by using copper ions (Cu 2+ ) in conjunction with the lead antimonate bindheimite, a yellow-colored opacifier. The introduction of small amounts of tin in the structure of bindheimite enabled the production of a ternary Pb–Sb–Sn oxide. Tin, which was most likely added with the copper source (bronze scrapings), is known to facilitate the crystallization of bindheimite. The results are consistent with the five scarabs and one scaraboid being manufactured in Egypt. This study, the first archeometric study of scarabs found in the Iberian peninsula, has greatly contributed to the understanding of the influence of the Eastern and Central Mediterranean world in the Southwestern Iberia during the first millennium B.C.